2008
DOI: 10.1017/s095026880700026x
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhoea prevention in a high-risk rural Kenyan population through point-of-use chlorination, safe water storage, sanitation, and rainwater harvesting

Abstract: Lack of access to safe water and sanitation contributes to diarrhoea moribidity and mortality in developing countries. We evaluated the impact of household water treatment, latrines, shallow wells, and rainwater harvesting on diarrhoea incidence in rural Kenyan children. We compared diarrhoea rates in 960 children aged <5 years in 556 households in 12 randomly selected intervention villages and six randomly selected comparison villages during weekly home visits over an 8-week period. On multivariate analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 26 publications
4
81
3
Order By: Relevance
“…Diarrhea is generally due to exposure to diarrhea-causing organisms which is mainly found in feaces. The practice of unsafe child feaces disposal contaminates the surrounding environment with human excreta which carries many infectious organisms that can cause enteric diseases such as childhood diarrhea [26][27][28]. This result was consistent with other reports, where environmental sanitations most often linked with the diarrhoea is refuse disposal [29][30][31].…”
Section: Discussionsupporting
confidence: 90%
“…Diarrhea is generally due to exposure to diarrhea-causing organisms which is mainly found in feaces. The practice of unsafe child feaces disposal contaminates the surrounding environment with human excreta which carries many infectious organisms that can cause enteric diseases such as childhood diarrhea [26][27][28]. This result was consistent with other reports, where environmental sanitations most often linked with the diarrhoea is refuse disposal [29][30][31].…”
Section: Discussionsupporting
confidence: 90%
“…Garrett et al [26] in Kenya showed that Diarrhoea risk was higher among shallow well user which was in accordance with the present study. Different findings were observed by Abdelateef [27], in which tap water in Gaza strip may be contaminated because the per cent of cases drinking tap water are more frequent than those in controls (11.4% in cases, 9.8% in controls).…”
Section: Discussionsupporting
confidence: 93%
“…Evaluations of these programs in Kenya have shown that use of the SWS was feasible, acceptable, and reduced diarrheal disease risk. [3][4][5] In 2003, Population Services International (PSI), a social marketing non-governmental organization , initiated a campaign to promote and sell the SWS solution, which was given the brand name WaterGuard; each bottle costs approximately $U.S. 0.26 and treats 1000 L of water.…”
Section: Introductionmentioning
confidence: 99%